2020
DOI: 10.2139/ssrn.3513061
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Awareness: Empirical Evidence for the European Union

Abstract: In this paper we assess public attitudes on climate change in Europe over the last decade. Using aggregate figures from the Special Eurobarometer surveys on Climate Change, we find that climate change attitudes have evolved according to the "S-shaped" information dissemination model, conditional to various socioeconomic and climatological factors. In particular, we find that environmental awareness is directly related to per capita income, social trust, secondary education, the physical distress associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…According to the Intergovernmental Science Policy Platform on Biodiversity and Ecosystem Services, 1 million plant and animal species are currently threatened with extinction (Jaspers, 2020). Moreover, GHG emissions are still increasing globally, with the projection that the carbon budget set to meet the Paris Agreement target of 2°C will be exhausted before 2050 (Baiardi and Morana, 2021). Consumer awareness of climate and biodiversity crisis continues to increase, leading to change in dietary habits and many questioning the sustainability of Western diets (Clonan et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Intergovernmental Science Policy Platform on Biodiversity and Ecosystem Services, 1 million plant and animal species are currently threatened with extinction (Jaspers, 2020). Moreover, GHG emissions are still increasing globally, with the projection that the carbon budget set to meet the Paris Agreement target of 2°C will be exhausted before 2050 (Baiardi and Morana, 2021). Consumer awareness of climate and biodiversity crisis continues to increase, leading to change in dietary habits and many questioning the sustainability of Western diets (Clonan et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer awareness of climate and biodiversity crisis continues to increase, leading to change in dietary habits and many questioning the sustainability of Western diets (Clonan et al ., 2015). In high-income societies, it is well-recognized that climate change and biodiversity loss are twin disasters and need to be addressed urgently (Baiardi and Morana, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These results reveal that all EU countries have become more aware of the climate change problem. Baiardi and Morana (2021) also indicated that climate change concern in Europe has increased over the last decade and significant effect are found for education, media coverage, social trust and relative power position of right-wing parties in government. Some authors (Nisbet and Myers 2007;Boykoff and Yulsman 2013) emphasises that public concern about climate change has risen recently due to growing scientific evidence and higher mass media coverage and political debate.…”
Section: The Correlation Between Changes In Climate Change Concern and Personal Responsibilitymentioning
confidence: 99%
“…The need for sustainability-oriented consumerism has been highlighted by the United Nations 2030 Agenda (Gillani and Kutaula, 2018) and awareness of this issue is increasing (Baiardi and Morana, 2020; Eurobarometer, 2021). However, this awareness is not always decisive for the adoption of sustainable food consumption.…”
Section: Introductionmentioning
confidence: 99%